High-throughput sequencing of Diatoms using V4 region of 18S rRNA gene in Bayug Island, Iligan City, Philippines - DARSHEL ESTER P. ESTOR; SHARON ROSE TABUGO (Society for Indonesian Biodiversity, 2023)
Abstract. Estor DEP, Tabugo SR. 2023. High-throughput sequencing of Diatoms using V4 region of 18S rRNA gene in Bayug Island, Iligan City, Philippines. Biodiversitas 24: 6343-6350. Diatoms are the main contributors to aquatic primary production and are the most dominant phytoplankton. Their adaptability and growth in diverse natural resources enable them to thrive in various climates and geographical areas, making them suitable for monitoring and biotechnology applications. This study aimed to analyze the diatom composition in two study sites: a mangrove area and the estuary in Bayug Island. The analysis was conducted using metabarcoding of the V4 region of the 18S rRNA gene, amplified and sequenced on the Illumina MiSeq platform. Four amplicon libraries were generated, representing the diatom composition at the two study sites. Data processing was performed using the Parallel-Meta-Suite software. Following quality control and processing, 20,433 amplicon sequence variants (ASVs) were obtained. Among these, the genera Navicula, Thalassiosira, Chaetoceros, Guinardia, Amphora, and Minidiscus were the most abundant ASVs. The assessment of diatom alpha diversity using the Shannon index indicated a higher diversity in the estuary site. Furthermore, the analysis done within the Parallel Meta Suite suggested that the presence of these specific diatom species can be linked to salinity levels, and may indicate environmental disturbances such as water pollution. The presence of these diatoms has the potential to be utilized in ecological treatments, disease prevention, biotechnology, and as nutrient indicators for other marine organisms. Physico-chemical parameters were recorded in the estuary area (S1), with the average water pH measuring around 7.6, salinity at approximately 36.6 ppt, and water temperature at 26.7?. In contrast, the measurements in the mangrove area (S2) revealed an average water temperature of 30?, salinity of around 35 ppt, and a water pH of 7.7. This research will serve as baseline data for diatom community in the area and a pioneering work on using NGS and eDNA for diatom study.